PROPERTY RIGHTS: A REVIEW ON RESOURCE ALLOCATION IN PRIVATE PROPERTY SYSTEM (Third Sector Social Economic Review, 2022)
The concept of “property rights” is a central concept in economics for it includes the rights to use resources in a society, the rights to earn income from resources, and the right to transfer these rights to others, thereby forming the basis of social distribution and allocation of resources. The issue of how and to what extent alternative allocations of property rights affect the use of resources and total output is an important area of research. In this study, property rights were first analyzed conceptually and it was stated that they could not be abstracted from their human and social dimensions. The focus of the study is the examination of the private property system in terms of resource allocation. In the private property system, it is accepted that the resources tend to be allocated among the highest value uses, and thus it is seen that property rights are considered in terms of ensuring economic efficiency. On the other hand, the existence of externalities, the argument that individual goals should not conflict with the maximization of social utility, and transaction costs; brings public ownership, state ownership and/or state intervention in the discussion. In this context, it can be stated that an important goal of the capitalist system is to achieve a structure that combines private and public ownership in resource allocation in a way that reduces the sum of transaction costs and the cost of externalities.
Keywords: Property Rights; Private Property System; Resource Allocation; Transaction Costs; Externalities